Business Administration and Business Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
In the framework of educational globalization and the growing power of international organizations in health and educational governance sector in the least developed countries (LDCs) have faced the latest stage of stress about whether their learning strategies should go behind the global educational models or seek out solutions of their diverse problems by encouraging restricted native literacy practices. This article presents an outline of (Least Developed Country) LDCs Asset in which there are several indicators, including health, school enrollment, and literacy. Economic growth has been elevated in the year leading to the economic crisis but remains weak. It repeatedly does not the advantage of the population at large, comes at high ecological costs, as shown by the rate of resource reduction and environmental damages, and youth unemployment remains very high. This article terminated with an appeal for developing circumstantially related literacy plans and policies throughout an asset point of view; and offers instructions for further research to investigate the Least Developed Countries literacy rate, school enrollment, and health policies.